Soldiers of the Cross : the story of the Church Army in Australia - Batley, A. W. (Alfred William) (Newcastle, N.S.W. : Church Army in Australia, 1959)
History of the evangelistic arm of the Church of England in Australia, the Church Army in Australia. Chapter 7: Colour opportunity, deals with the Army's work amongst Aboriginal people: "...Missions are the Aborigines' only hope of survival."
Originally published 1955 under title: The boomerang returns.
Keywords: Church Army in Australia; Religions - Christianity - Anglican Church; Religions - Christianity - Missionaries; Religions - Christianity - Missions